Imam dan Dialog Sosialnya (Analisis Kritis Program TAPERA “Tabungan Perumahan Rakyat” Bagi Kehidupan Umat di Paroki Riam Batang Kalimantan Tengah) - Yohanes Makias De (Jurnal Pendidikan Agama dan Teologi, 2024)
This research analyzes the role of priests in social dialogue related to the implementation of the Public Housing Savings Program (TAPERA) in Riam Batang Parish and its impact on the lives of the people. TAPERA, as an Indonesian government initiative, aims to facilitate livable house ownership for low-income people through savings and financing schemes. In Riam Batang Parish, priests not only function as spiritual leaders, but also as facilitators of social dialogue and agents of change. This research uses a qualitative approach with case studies, collecting data through in-depth interviews with priests and congregation. The research results show that imams play a key role in increasing people's awareness and understanding of TAPERA, as well as helping overcome bureaucratic and economic obstacles. The Imam plays an active role in providing education and outreach regarding this program, helping the congregation access its benefits, and being a mediator between the congregation and government agencies. However, several challenges such as lack of understanding of the people, complicated administrative processes, and economic limitations are still significant obstacles. This research highlights the importance of effective social dialogue built by priests in supporting the implementation of TAPERA, as well as the need for collaboration between the church, government and local communities to overcome these challenges. Thus, the role of the priest in a social and economic context becomes essential in improving the welfare of the people and achieving the goals of a more inclusive and sustainable public housing program.